Postimplantation ventricular ectopic burden and clinical outcomes in cardiac resynchronization therapy‐defibrillator patients: a MADIT‐CRT substudy. Issue 2 (20th September 2017) - Ruwald, Anne‐Christine; Aktas, Mehmet K.; Ruwald, Martin H.; Kutyifa, Valentina; McNitt, Scott; Jons, Christian; Mittal, Suneet; Steinberg, Jonathan S.; Daubert, James P.; Moss, Arthur J.; Zareba, Wojciech
Abstract : Background: Frequent ventricular ectopy on preimplantation Holter has been associated with attenuated benefit from cardiac resynchronization therapy (CRT). However, it is unclear whether ectopic burden measured post‐CRT implantation can be utilized to evaluate long‐term prognosis. We aimed to describe the association between post‐CRT implantation ectopic burden and subsequent risk of clinical outcomes. Methods: At the 12‐month follow‐up visit, 24‐hour Holter recordings were performed in 698 CRT‐D patients from the MADIT‐CRT study. The mean number of ventricular premature complexes (VPCs/hour) was calculated. High ectopic burden was defined as >10 VPCs/hour and low burden as ≤10 VPCs/hour. Multivariate Cox proportional hazards models were utilized to assess the association between 12‐month ectopic burden and the risk of the end points of heart failure (HF) or death and ventricular tachyarrhythmias (VT/VF). Results: At 12 months, 282 (40%) patients presented with low ectopic burden and 416 (60%) patients presented with high ectopic burden. The 3‐year risk of HF/death and VT/VF was lower in patients with a low burden (7% and 8%) and significantly higher (25% and 24%) in patients with high burden. In multivariate analyses, patients with a high ectopic burden had approximately threefold increased risk of both HF/death (HR=2.76 [1.62–4.70], p < .001) and VT/VF (HR=2.79 [1.69–4.58], p < .001). Conclusion: In CRT‐D patients with mild heart failure, high ectopic burden at 12‐month follow‐up was associated with a high 3‐year risk of HF/death and VT/VF and threefold increased risk as compared to patients with low burden. Ectopic burden at 12 months may be a valuable approach for evaluating long‐term prognosis.